2009
DOI: 10.1080/00224490902747701
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Individual Differences in Pornography Use: Theoretical Perspectives and Implications for Treating Sexual Offenders

Abstract: This article reviews the extant literature regarding pornography's influence on antisocial attitudes, sexual arousal, and sexually aggressive behavior in both noncriminal and criminal samples. The article concludes that when examined in the context of multiple, interacting factors, the findings are highly consistent across experimental and nonexperimental studies and across differing populations in showing that pornography use can be a risk factor for sexually aggressive outcomes, principally for men who are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 82 publications
5
91
1
5
Order By: Relevance
“…There is reason to believe that research on hypergender orientations among adults may extend to adolescents. For instance, one study showed that adolescent girls' responses to sexually explicit internet material depended on their hypergender orientation (van Oosten, 2016), similar to young adult men (e.g., Kingston, Malamuth, Fedoroff, & Marshall, 2009) and women (e.g., van Oosten et al, 2015b). In addition, an increased hypergender orientation predicts adolescent girls' initiation of the use of sexually explicit internet material (Vandenbosch & Peter, 2016), and both adolescent boys' and girls' selection of certain types of sexually explicit material (i.e., violent pornography, Vandenbosch, 2015).…”
Section: Predicting Adolescents' (Exposure To) Sexy Self-presentationmentioning
confidence: 99%
“…There is reason to believe that research on hypergender orientations among adults may extend to adolescents. For instance, one study showed that adolescent girls' responses to sexually explicit internet material depended on their hypergender orientation (van Oosten, 2016), similar to young adult men (e.g., Kingston, Malamuth, Fedoroff, & Marshall, 2009) and women (e.g., van Oosten et al, 2015b). In addition, an increased hypergender orientation predicts adolescent girls' initiation of the use of sexually explicit internet material (Vandenbosch & Peter, 2016), and both adolescent boys' and girls' selection of certain types of sexually explicit material (i.e., violent pornography, Vandenbosch, 2015).…”
Section: Predicting Adolescents' (Exposure To) Sexy Self-presentationmentioning
confidence: 99%
“…The majority of researchers exploring associations between SEM use and sexual behaviors focus on sexual violence (e.g., Malamuth et al, 2000), finding associations between SEM use and increased sexual perpetration and aggression, the trivialization of criminal behavior (e.g., rape), and increased risk for sexual deviancy (Kingston, Malamuth, Fedoroff & Marshall, 2009;Manning, 2006). Several studies have explored associations between SEM use and sexual risk behaviors, finding that adolescents and young adults who use SEM tend to have more sexual partners, to have used alcohol or another substance at their last sexual encounter, to not have used contraception during sexual intercourse, and to have had an STD (Braun-Courville & Rojas, 2009;Carroll et al, 2008;Haggstrom-Nordin, Hanson, & Tyden, 2005;Wingood et al, 2001).…”
Section: Sem Use and Sexual Behaviors Satisfaction And Preferencesmentioning
confidence: 99%
“…Previous behavior genetics studies have already found genetic influences on how often people use other evolutionarily novel technologies, including viewing television (Plomin, Corley, Defries, & Fulker, 1990;Rowe & Herstand, 1986;Sherry, 2001) and reading books (Friend et al, 2009;Harlaar et al, 2007;Martin et al, 2009) -just as pharmacogenomics studies have found substantial genetic influences on people's responsiveness to recently discovered psychiatric drugs for depression and schizophrenia (Daly, 2010). Also, personality traits known to be heritable influence usage patterns for every communication medium analyzed so far, including television, movies, music, art, books, email, online gaming, social networking sites, and chat rooms (Anolli et al, 2005;Chamorro-Premuzic et al, 2009;Finn, 1997;Hertel et al, 2008;Jeng & Teng, 2008;Kingston et al, 2009;Kraaykamp & van Eijck, 2005;Krcmar & Kean, 2005;Landers & Lounsbury, 2006;McManus & Furnham, Geoffrey Miller, Gu Zhu, Margaret J. Wright, Narelle K. Hansell, and Nicholas G. Martin 2006;Persegani et al, 2002;Ross et al, 2009;Sherry, 2001;Shim & Paul, 2007). Many of these heritable personality traits -especially extraversion, impulsivity, and neuroticism -also influence normal and addictive use of mobile phones (Arns, Van Luijtelaar, Sumich, Hamilton, & Gordon, 2007;Butt & Phillips, 2008;Ehrenberg et al, 2008).…”
mentioning
confidence: 99%